Pengaruh E-Commerce, Inovasi Produk Dan Modal Usaha Terhadap Peningkatan Pendapatan UMKM Di Kabupaten Pasuruan : Studi Pada UMKM Di Kabupaten Pasuruan - Santi Nurmalasari (FEB Universitas Maritim Semarang, 2023)
The purpose of this study was to find out how much influence E-Commerce (X1), Product Innovation (X2) and Business Capital (X3) have on Increasing Income (Y). This study uses an explanatory research approach with quantitative methods. The data collection for this research was by distributing questionnaires to 100 respondents. The data analysis technique uses SPSS software version 25, in which the data will be processed, described and discussed to answer and prove the proposed hypotheses.The research results are as follows: (1). E-Commerce (X1) has a positive and significant effect on increasing income (Y). (2). Product Innovation (X2) has a positive and significant effect on Increasing Income (Y). (3). Business capital (X3) has a positive and significant effect on increasing income (Y). (4). E-Commerce (X1), Product Innovation (X2) and Business Capital (X3) simultaneously (together) have a positive and significant effect on Increasing Income (Y).